How to translate culture-bound references: a case study of Turespaña’s tourist promotion campaign - Cómitre Narváez, Isabel; Valverde Zambrana, José María (The Journal of Specialised Translation, 2014)
One of the greatest challenges for the translator is the rendering of culture-specific items ─ traditionally regarded as a potential source of untranslatability. Many scholars have discussed this issue and different approaches have been described within the discipline of Translation Studies. The paper focuses on the translation of culture-specific items in tourist promotion campaigns, demonstrating how these items call for specific translation treatment. The material for analysis has been sourced directly from the Instituto de Turismo de España (Turespaña), the Spanish Tourist Board, and specifically the international tourist promotion campaign, Spain marks, where culture-specific items are used as a sales argument to promote Spain worldwide as a tourist destination. In the present study, we will review the literature concerning cultural aspects within the framework of Translation Studies. Then, we will examine the procedures for translating culture-specific items in the Spanish source texts and their corresponding English versions of the campaign. A short survey will shed light on the success of the Spain marks campaign. The paper concludes with some remarks about the role of the translator in the field of tourist promotion campaigns.